2018
DOI: 10.1002/ejic.201801002
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reactivity of Copper Acetylacetone Bis(Thiosemicarbazone) Complexes

Abstract: The complexation reaction mechanism of acetylacetone bis-thiosemicarbazone ligands (H 2 acacR) with Cu II is explored using a variety of physical methods. The complexes form via a complicated multistep mechanism that is initiated by ring opening of the pyrazoline form of the ligand and leads, ultimately in air, to an oxidised ketone form of the ligand. Tetradentate N 2 S 2 coordinated forms of the intermediate [Cu (acacR)] [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…5a, b) are very similar and the most prominent features to emerge in the final products are a very broad maximum around 780 nm and a shoulder around 440 nm, which was also seen in the [Cu-(acacR)]series. [4] For [Cu II (banphe)] - (Figs 4c and 5c) a much more intense maximum appears at 440 nm with a shoulder at 460 nm. This transition must be linked with the N-phenyl chromophore.…”
Section: Copper Complexationmentioning
confidence: 91%
See 4 more Smart Citations
“…5a, b) are very similar and the most prominent features to emerge in the final products are a very broad maximum around 780 nm and a shoulder around 440 nm, which was also seen in the [Cu-(acacR)]series. [4] For [Cu II (banphe)] - (Figs 4c and 5c) a much more intense maximum appears at 440 nm with a shoulder at 460 nm. This transition must be linked with the N-phenyl chromophore.…”
Section: Copper Complexationmentioning
confidence: 91%
“…Previous work with the H 3 acacR ligands [4] has shown that their complexation reactions with Cu II are complicated and involve several steps. They are also affected by the presence of oxygen.…”
Section: Copper Complexationmentioning
confidence: 99%
See 3 more Smart Citations